Karyotype analysis of some species of Vicia L. section Vicia (Fabaceae Lindl.) in Iran - Nastaran Jalilian; Mohammad Reza Rahiminejad Ranjbar (تاکسونومی و بیوسیستماتیک, 2011)
The somatic chromosome numbers and karyotypic analysis of six taxa belonging to Vicia sect. Vicia (Fabaceae) were performed. We found three basic chromosome numbers (x=5, 6 and 7) in this section. All of the taxa were diploid. The chromosome number of V. lathyroides, V. grandiflora, V. sativa var. cordata and V. sativa var. amphicarpa were presented for the first time in Iran. Karyotype formula was different in the taxa, so that in the taxa V. lathyroides (2n=12), V. sativa var. sativa (2n=12), V. sativa var. angustifolia (2n=12), V. sativa var. cordata (2n=10), V. sativa var. amphicarpa (2n=14), V. grandiflora (2n=14) karyotype the formula were 6st, 2m+4st, 1m+1sm+4st, 5st, 3sm+4st and 5sm+2st respectively. The taxa studied were placed in 3A (V. sativa var. angustifolia and V. grandiflora), 3B (V. sativa var. amphicarpa) and 4A (V. lathyroides, V. sativa var. sativa and V. sativa var. cordata) classes of Stebbines. Based on A1 and A2 parameters, V. grandiflora and V. sativa var. cordata had symmetrical and asymmetrical karyotypes respectively.